تسيير المجالس الشعبية المنتخبة في ظل التعددية الحزبية - خولة سعايدية (My University, 2020)
Summary The Algerian legislator adopted a system of elected councils from independence to the present day, and these councils passed through two stages: the pre-pluralism stage, which resulted in two councils at the local level: the Municipal People’s Council, and the State People’s Council, and at the national level there was one council called the National Shi’a Council. As for the pluralism phase, the legislator maintained the same councils present at the local level. At the national level, a second chamber was created alongside the National People’s Assembly called the “Nation Council.” The pluralism phase was characterized by new principles and directives established by the 1989 Constitution by abolishing the one-party system and adopting the multi-party system. And economic openness. This pluralistic system had its effects on the elected councils, as the circumstances required a law that responded to the variables and requirements of the stage. This stage witnessed exceptional cases in the councils, which showed the limitations of a legal system that was unable to resolve tensions, and its inability to settle problems of a new type, resulting especially from pluralism that was still on the way to growth. Hence, it became necessary to make amendments to the legislative system governing these councils. The 1996 Constitution was issued. This constitution came to enhance the role of the elected councils in managing development and public affairs. Several amendments were made to this constitution, the last of which was in 2016. Its requirements were implemented through the issuance of Organic Law No. 16-12, which defines the organization of the National People’s Assembly. And the National Assembly, and their work, as well as the functional relations between them and the government, and the bylaws of the National Assembly 2017. As for the bylaws of the National People’s Assembly, it was in turn presented to Parliament in 2018 for discussion, but it has not seen the light until now. As for the local level, this work was embodied through Issuance of the law relating to the municipality in 2011 and the law relating to the state in 2012 , ,,,,,,,,,,,,,,,,,,, الملخص تبنى المشرع الجزائري نظام المجالس المنتخبة منذ الاستقلال إلى يومنا هذا، ومرت هذه المجالس بمرحلتين: مرحلة ما قبل التعددية نتج عنها مجلسين على المستوى المحلي تمثلا في: المجلس الشعبي البلدي، والمجلس الشعبي الولائي، وعلى المستوى الوطني كان هناك مجلس واحد يسمى المجلس الشعي الوطني. أما بالنسبة لمرحلة التعددية فقد حافظ المشرع على نفس المجالس المتواجدة على المستوى المحلي أما على المستوى الوطني فقد تم استحداث غرفة ثانية إلى جانب المجلس الشعبي الوطني تسمى "مجلس الأمة" تميزت مرحلة التعددية الحزبية بمبادئ وتوجيهات جديدة أرساها دستور1989 بإلغاء نظام الحزب الواحد واعتماد نظام التعددية الحزبية والإنفتاح الإقتصادي ، وكان لهذا النظام التعددي أثاره على المجالس المنتخبة ، إذ كانت الظروف تتطلب قانونا يستجيب إلى متغيرات المرحلة ومتطلباتها. وقد عرفت هذه المرحلة حالات استثنائية على المجالس ، أظهرت محدودية منظومة قانونية غير قادرة على تفكيك التوترات ، وعدم تمكنها من تسوية المشاكل ذات النمط الجديد ، الناجمة خاصة عن تعددية ما تزال في طريق النمو ومن هنا بات من ضروري إجراء تعديلات على المنظومة التشريعية المسيرة لهذه المجالس، فصدر دستور 1996 ، لقد جاء هذا الدستور من أجل ترقية دور مكانة المجالس المنتخبة في تسيير التنمية والشؤون العامة، وتوالت على هذا الدستور عدة تعديلات كان أخرها 2016 ، وتم تنزيل مقتضياته من خلال صدور القانون العضوي رقم 16-12 الذي يحدد تنظيم المجلس الشعبي الوطني ومجلس الأمة ، وعملهما ، وكذا العلاقات الوظيفية بينهما وبين الحكومة، والنظام الداخلي لمجلس الأمة 2017، أما النظام الداخلي للمجلس الشعبي الوطني فقد عرض بدوره على البرلمان سنة 2018 لمناقشته ، إلا أنه لم يرى النور لحد الساعة ،أما على المستوى المحلي تجسد هذا العمل من خلال إصدار القانون المتعلق بالبلدية سنة 2011 والقانون المتعلق بالولاية لسنة 2012 , ,,,,,,,,,,,,,,,,,,,,,,,, Résumé Le législateur algérien a adopté un système de conseils élus depuis l'indépendance jusqu'à nos jours, et ces conseils sont passés par deux étapes : l'étape du pré-pluralisme, qui a abouti à deux conseils au niveau local : le Conseil populaire municipal et le Conseil populaire d'État. , et au niveau national, il y avait un conseil appelé Conseil national chiite. Quant à la phase de pluralisme, le législateur a maintenu les mêmes conseils présents au niveau local. Au niveau national, une deuxième chambre a été créée à côté de l'Assemblée populaire nationale appelée « Conseil de la Nation ». La phase de pluralisme a été caractérisée par de nouveaux principes et directives. établi par la Constitution de 1989 en abolissant le système de parti unique et en adoptant le multipartisme. Et l'ouverture économique, et ce système pluraliste, ont eu leurs effets sur les conseils élus, car les circonstances exigeaient une loi qui réponde aux variables et aux exigences de La scène. Cette étape a été marquée par des cas exceptionnels au sein des conseils, qui ont montré les limites d'un système juridique incapable de résoudre les tensions et son incapacité à résoudre des problèmes d'un type nouveau, résultant notamment d'un pluralisme encore en voie de croissance. il est devenu nécessaire d'apporter des amendements au système législatif régissant ces conseils. La Constitution de 1996 a été publiée. Cette constitution est venue renforcer le rôle des conseils élus dans la gestion du développement et des affaires publiques. Plusieurs amendements ont été apportés à cette constitution, dont le dernier C'était en 2016. Ses exigences ont été mises en œuvre par la promulgation de la loi organique n° 16-12, qui définit l'organisation de l'Assemblée populaire nationale et de l'Assemblée nationale, et son travail, ainsi que les relations fonctionnelles entre elles et le gouvernement. , et les statuts de l'Assemblée nationale 2017. Quant aux statuts de l'Assemblée populaire nationale, ils ont été à leur tour présentés au Parlement en 2018 pour discussion, mais ils n'ont pas vu le jour jusqu'à présent. Quant au niveau local, ces travaux s'est concrétisée par la promulgation de la loi relative à la commune en 2011 et de la loi relative à l'État en 2012